Conducting Web-based survey research: a lesson in Internet designs. - Daley EM; McDermott RJ; Brown KRM; Kittleson MJ (American Journal of Health Behavior)
OBJECTIVES: To examine the tacit knowledge resulting from designing a complex Web site to facilitate administration of an Internet-based survey. METHODS: Formative methods guided studying the feasibility of conducting an online survey using versions of the Keirsey Temperament Sorter II and the National College Health Risk Behavior Survey. RESULTS: Web-site design software and pilot testing were critical to success. Incorporating the target audience as consumers in both Web site development and formative evaluation simplified data collection and analysis. CONCLUSIONS: Online instrumentation used in survey research is both practical and desirable. Future refinements are necessary, but improved designs can emanate from this particular effort.